2022
DOI: 10.3390/biomedicines10081894
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Kidney Disease in Boys with Posterior Urethral Valves–Pathogenesis, Prognosis and Management

Abstract: Posterior urethral valves (PUV) are the most common form of lower urinary tract obstructions (LUTO). The valves can be surgically corrected postnatally; however, the impairment of kidney and bladder development is irreversible and has lifelong implications. Chronic kidney disease (CKD) and bladder dysfunction are frequent problems. Approximately 20% of PUV patients will reach end-stage kidney disease (ESKD). The subvesical obstruction in PUV leads to muscular hypertrophy and fibrotic remodelling in the bladder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 86 publications
0
11
0
Order By: Relevance
“…Other possible prognostic factors include echographic parameters, urinary and biochemical markers, prenatal parameters, and proteomic data. Klaus et al concluded that the best postnatal predictor for progression to CKD was nadir serum creatinine after valve ablation, while the values of other urinary markers beyond microalbuminuria were poor, and novel postnatal biomarkers should be further investigated ( 42 , 17 ). The final validation of the 12PUV signature is ongoing in the first clinical proteomics study in prenatal medicine.…”
Section: Discussionmentioning
confidence: 99%
“…Other possible prognostic factors include echographic parameters, urinary and biochemical markers, prenatal parameters, and proteomic data. Klaus et al concluded that the best postnatal predictor for progression to CKD was nadir serum creatinine after valve ablation, while the values of other urinary markers beyond microalbuminuria were poor, and novel postnatal biomarkers should be further investigated ( 42 , 17 ). The final validation of the 12PUV signature is ongoing in the first clinical proteomics study in prenatal medicine.…”
Section: Discussionmentioning
confidence: 99%
“…The long-term implications of improved bladder health in LUTO cases may have significant downstream effects on the kidneys, as some of the long-term renal deterioration in these patients can be directly related to an end-stage high pressure poorly compliant bladder. 47 Based on prior studies and the current bench-top performance of our one-way valve fetal shunt, we anticipate a significant urologic benefit that will favor the placement of shunts in a wider range of LUTO patients, including LUTO cases with normal amniotic fluid volume, which have also shown an increased risk of worsening renal functional and need of renal replacement therapy later in life. Cases of LUTO with normal amniotic fluid volume are not generally considered candidates for VAS.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst the prevalence of UTIs was common in women in this study, the risk of MDR infection was significantly higher in males compared to women. UTIs in males are usually associated with a urological abnormality, such as prostatic hyperplasia or posterior urethral valves that are usually associated with instrumentation and risk of infection [ 36 , 37 , 38 ]. Lastly, the highest risk of MDR was found in patients with the presence of antibiotics in the urine.…”
Section: Discussionmentioning
confidence: 99%